Environmental Jurisprudence and the Supreme Court - "Sahu,Geetanjoy" (New Delhi, 2014)
Since the 1980s, the Supreme Court of India has intervened regularly in cases involving environmental issues, taking both state and private actors to task on environmentally destructive actions and policies and asserting itself in the implementation of its judgments. It has thus earned itself a widespread and formidable reputation as a 'green court'.
Keywords: India-Supreme Court